Nonoperative Management of Proximal Tibiofibular Joint Synostosis after Tibial Intramedullary Nailing. (30th May 2019) - Ebbott, David C.; Johnson, Alexander J.; Haydel, Christopher
Abstract : We report the case of a 28-year-old male semiprofessional basketball player who presented to an outside hospital with nonhealing stress fractures for which he underwent tibial intramedullary nailing (IMN). Two weeks after surgery, he developed pain proximal and lateral to the knee. As he returned to play, the pain worsened with jumping and lateral movement and improved with rest. He presented to our hospital one year after the operation with the same unresolved pain. Imaging one year after the surgery revealed proximal tibiofibular joint (TFJ) synostosis aligned with the drill path. Literature review showed that rare noncongenital cases of proximal TFJ synostosis cases were most often treated nonoperatively. However, two cases involved the removal of excessively protruding screws and two cases involved bone resection that resolved painful disruption of other joints, such as the ankle. The current patient had proper implant positioning and no other impacted joints, so he was managed without operative intervention. By the final 16-month postoperative follow-up, his symptoms had resolved completely. Although an unusual occurrence with limited data, we recommend nonoperative management for proximal TFJ synostosis caused by tibial nailing if implants are properly positioned and no other joints are affected.